Preliminary evidence for small-fiber neuropathy in fibromyalgia patients. Issue 2 (April 2008) - Staud, Roland
Kim SH, Kim DH, Oh DH, Clauw DJ: Characteristic electron microscopic findings in the skin of patients with fibromyalgia –– preliminary study. Clin. Rheumatol. 27(3), 407––411 (2008). Peripheral tissue abnormalities may contribute to the increased pain sensitivity of fibromyalgia (FM) patients. To address this issue, the authors obtained skin biopsies from the deltoid region of 13 FM patients and five healthy, pain-free control subjects. After fixation, all tissues were examined using electron-microscopy (EM) by an investigator who was blinded to the participants'' diagnosis. In contrast to healthy controls, the skin biopsies from nine out of 13 FM patients showed axons that were localized to the periphery of unmyelinated Schwann cell sheaths. These findings were associated with ballooning of Schwann cells, diminished folding of Schwann cell sheaths and smaller axonal size. Myelinated nerve fibers were unremarkable. The EM findings of this study show that the cutaneous nerve endings of FM patients possess unusual architecture, as well as ballooning of their associated Schwann cells. Similar changes were not detectable in skin biopsies of healthy pain-free controls.